Promotion of self-learning by means of Open Educational Resources and semantic technologies - Pallares Rivera, J. (2017)
Open Educational Resources (OER) have the potential to encourage self-learning and lifelong learning. However, there are some barriers that make it difficult to find the suitable information. The successful adoption of OER in processes of informal or self-directed learning will depend largely on what the learner is able to reach without a guide or a tutor. However, the OERs quality and their particular features can positively influence into the motivation of the self-learner to achieve their goals. In this paper, the authors present an approach to enhance the OER discovery by self-learners. This is designed to leverage open knowledge sources, which are described by semantic technologies. User's data and OER encoded in formal languages can be linked and thus find paths for suggest the most appropriate resources.